Effective decrease of photoelectric emission threshold from gold plated surfaces - Wass,PJ; Hollington,D; Sumner,TJ; Yang,F; Pfeil,M (Review of Scientific Instruments, 2019)
Many applications require charge neutralization of isolated test bodies, and this has been successfully done using photoelectric emission from surfaces which are electrically benign (gold) or superconducting (niobium). Gold surfaces nominally have a high work function (∼5.1 eV) which should require deep UV photons for photoemission. In practice, it has been found that it can be achieved with somewhat lower energy photons with indicative work functions of (4.1–4.3 eV). A detailed working understanding of the process is lacking, and this work reports on a study of the photoelectric emission properties of 4.6 × 4.6 cm2 gold plated surfaces, representative of those used in typical satellite applications with a film thickness of 800 nm, and measured surface roughnesses between 7 and 340 nm. Various UV sources with photon energies from 4.8 to 6.2 eV and power outputs from 1 nW to 1000 nW illuminated ∼0.3 cm2 of the central surface region at angles of incidence from 0° to 60°. Final extrinsic quantum yields in the range 10 ppm–44 ppm were reliably obtained during 8 campaigns, covering a period of ∼3 years but with intermediate long-term variations lasting several weeks and, in some cases, bake-out procedures at up to 200 °C. Experimental results were obtained in a vacuum system with a baseline pressure of ∼10−7 mbar at room temperature. A working model, designed to allow accurate simulation of any experimental configuration, is proposed.